Accepted Manuscripts (Quarterly Journal of Economics, 1987)
Accepted Manuscripts Get access The Quarterly Journal of Economics, Volume 102, Issue 1, February 1987, Pages 173–177, https://doi.org/10.1093/qje/102.1.173 Published: 01 February 1987